Your brand is not your logo : it is an experience that lives in your customer's gut - Brunner, Robert, 1958- (FT Press Delivers elements., 2010)
"This Element is an excerpt from Do you matter?: how great design will make people love your company (ISBN: 9780137142446) by Robert Brunner and Stewart Emery. Lessons from the legendary Harley-Davidson: build a brand experience that takes on a life of its own!"--Resource description page.